7 Tesla MR Imaging: Opportunities and Challenges - Umutlu, L.; Ladd, M. E.; Forsting, M.; Lauenstein, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
The urge to increase magnetic field strength is driven by a number of potentially beneficial physical changes, possibly resulting in improved MR diagnostics. With the successful introduction of in-vivo ultra-high-field MR imaging, by means of 7 Tesla MRI, the focus of scientific research has been set on compiling different applications of brain and body imaging. This review presents an overview on the current status of 7 T MR imaging, investigating the opportunities as well as challenges associated with ultra-high-field MRI.Citation Format:• Umutlu L, Ladd ME, Forsting M et al. 7 Tesla MR Imaging: Opportunities and Challenges. Fortschr Röntgenstr 2014; 186: 121 – 129
Keywords: MR imaging; technical aspects; diagnostic radiology